G471(P) Challenges and benefits of paediatric advance care planning: a mixed methods systematic review and narrative synthesis. (May 2019) - Box, D; Fraser, L; Beresford, B
Abstract : Aims: To present the narrative synthesis of a systematic review on the challenges and benefits of paediatric advance care planning (pACP). Methods: Three electronic databases (MEDLINE, CINAHL and PsycINFO were searched from January 1995 to May 2018 for eligible quantitative, mixed methods and qualitative papers. Themes from the findings of the included papers were generated and a thematic synthesis completed. Results: A total of 12 094 papers were identified and after applying a priori inclusion and exclusion criteria, 49 papers were included in the review. In relation to the review questions, themes and subthemes were identified and synthesised as shown in the table 1 : Roles within consultations Conclusion: The findings of this comprehensive systematic review reflect the complexity of paediatric advance care planning, with evidence to support the benefits of it and the ongoing challenges from the different stakeholder perspectives.